Kajian Pustaka Komparatif Protokol Komunikasi Internet of Things Berdasarkan Latensi, Efesiensi Energi, dan Skalabilitas - Afriansyah Saputra, Muhammad Yudis; Yulindon Yulindon (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study presents a comparative literature review of Internet of Things (IoT) communication protocols, focusing on latency, energy efficiency, and scalability. The rapid development of IoT applications requires efficient communication mechanisms capable of handling constrained devices and large-scale networks. This research adopts a Systematic Literature Review (SLR) approach by analyzing relevant studies published between 2021 and 2026 from reputable databases such as Scopus, IEEE Xplore, ScienceDirect, and MDPI. The results indicate that no single protocol outperforms others across all performance parameters. CoAP demonstrates superior performance in latency and energy efficiency due to its lightweight UDP-based communication. MQTT provides stable latency and high scalability through its publish–subscribe architecture, making it suitable for large-scale IoT systems. Meanwhile, HTTP/HTTPS offers high interoperability but suffers from higher latency and energy consumption. The findings highlight the importance of selecting communication protocols based on specific application requirements. This study contributes by providing an integrated comparative analysis that considers multiple performance aspects simultaneously, offering a more comprehensive perspective for IoT system design